Rancang Bangun Sistem Ujian Online Berbasis Web dengan Koreksi Otomatis dan Pengawas Aktivitas Menggunakan Metode Agile - Maulana Hafizh Ilham; Muhammad Rivaldo Yames; Taraka Bhanu Widijanto; Wasis Haryono (CV. Multi Kreasi Media, 2025)
Exams are one of the important evaluation methods in the world of education to measure students' understanding and competence. Along with the development of technology, examination activities have undergone many changes where manual examination activities are no longer routine activities in examinations, especially at this time. However, there are still many educational institutions that hold examinations manually or use systems that are not yet integrated, so that their implementation is less effective, time-consuming, and prone to administrative errors. To overcome these problems, this study aims to design and build a Web-Based Online Examination Application using the PHP programming language and the Codeigniter framework. This application is expected to make it easier for organizers to manage exam question data, manage exam schedules, manage classes, manage student data and produce information in the form of exam score data reports. System development is carried out using the Agile method, which allows the software development process to be carried out iteratively and adaptively to changing needs, by involving continuous user feedback at every stage. With the implementation of this online examination application, it is hoped that a modern, fast, and accurate evaluation system will be created, and support digital transformation in the world of education.